2016
DOI: 10.1186/s40100-016-0066-5
|View full text |Cite
|
Sign up to set email alerts
|

Demand relationships in orange exports to Russia: a differential demand system approach focusing on Egypt

Abstract: Recent years have witnessed closer diplomatic relations between Egypt and Russia, which have led to significant growth in the countries' bilateral agricultural trade. As a world-leading producer and exporter of oranges, these developments represent an opportunity for Egypt to promote its orange exports to Russia. Another emerging opportunity for Egypt to increase its share in the Russian market for imported oranges has been provided by import embargos imposed by Russia in recent years on agricultural and food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…On the export side, the import demand for food commodities (especially fresh fruit and vegetables) by Russia, and to a lesser extent in Ukraine, has been growing over the past two decades, fuelled by increases in real disposable incomes and the growing Strategic Review for Southern Africa, Vol 44 No 1 2022 ISSN 1013-1108 tendency among domestic consumers to maintain healthier diets (Abu Hatab 2016). This offered export opportunities to small producers and exporters in many African countries (e.g., Egypt, Morocco and Kenya) to increase their market share in the Russian and Ukrainian markets for imported horticultural commodities.…”
Section: Pathways Through Which the Russia-ukraine Crisis Threatens A...mentioning
confidence: 99%
“…On the export side, the import demand for food commodities (especially fresh fruit and vegetables) by Russia, and to a lesser extent in Ukraine, has been growing over the past two decades, fuelled by increases in real disposable incomes and the growing Strategic Review for Southern Africa, Vol 44 No 1 2022 ISSN 1013-1108 tendency among domestic consumers to maintain healthier diets (Abu Hatab 2016). This offered export opportunities to small producers and exporters in many African countries (e.g., Egypt, Morocco and Kenya) to increase their market share in the Russian and Ukrainian markets for imported horticultural commodities.…”
Section: Pathways Through Which the Russia-ukraine Crisis Threatens A...mentioning
confidence: 99%
“…Otherwise, the navel orange export season in Egypt runs from mid-November to mid-February [4] [22] and for a high economic return, navel oranges tend to extend the harvest period by leaving the fruit on the trees for longer periods of time in order to extend the marketing season. This procedure causes the aforementioned disorders to appear, reducing its shelf life and marketing ability.…”
Section: Economic Indicators Of Washington Navel Orangementioning
confidence: 99%
“…coffee EU's import demand for fresh potato and cotton) towards horticultural commodities, especially fresh and processed fruit and vegetables (Karing'u et al, 2021). Previous research has shown that developing the horticultural export industry and linking smallholder farmers to high-value markets are crucial for LMICs' development agenda through creating jobs and income-generating activities in farming communities, and contributing to poverty alleviation and food security (Abu Hatab, 2016;Mwambi et al, 2016). Therefore, in recent decades, many LMICs have implemented policies to promote horticultural exports and prioritized the modernization of the horticultural sector as an export diversification and poverty reduction strategy (Abu Hatab and Hess, 2013;Annor et al, 2016).…”
Section: Introductionmentioning
confidence: 99%